Edukasi Perhitungan Harga Pokok Produksi untuk Menentukan Harga Jual Pempek Cek Ha - Sayadi, Muhammad Hamdan (Rahmatan Lil 'Alamin Journal of Community Services, 2026)
MSMEs are important instruments in Indonesia’s economy and play a significant role in reducing poverty. The success of MSMEs is strongly influenced by business owners’ ability to manage finances, particularly in calculating the cost of goods manufactured. Errors in calculating production costs may lead to inappropriate selling prices and potential financial losses. This activity applied an educational method to improve partners’ understanding and skills through a systematic learning process, beginning with data collection and continuing to production cost calculation practices. Information related to the pempek production process was analyzed to identify cost components, calculate production costs, and determine appropriate selling prices. The analysis showed that partners still set selling prices based on estimates and assumptions without accurate calculations. This condition indicates limited understanding of proper pricing methods and the actual production costs of small pempek, highlighting the need for continuous assistance to support more effective and profitable pricing decisions.